Eco-terrorists Facing Armageddon: The Defence of Necessity and Legal Normativity in the Context of Environmental Crisis - Tremblay, Hugo (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
The invocation of necessity as a defence for acts of civil disobedience has raised questions about the rule of law and legal certainty. The rise of radical environmental activism in the context of climate change warrants an inquiry into the scope and limitations of the defence in Canada. This paper argues that the defence of necessity significantly increases legal flexibility in Canadian environmental law. To some extent, the defence may thus enhance the law’s resilience to socio-ecological changes. However, the defence could also render the law flexible to such an extent that positive norms might lose their prescriptive value in certain circumstances. In particular, as the link connecting human activity, climate change, and consequent damage to the environment becomes clearer, there is a greater likelihood of environmental activists successfully invoking necessity to defend illegal acts aimed at curbing environmental degradation. In other words, necessity may offer a defence against the enforcement of legal frameworks de facto authorizing catastrophic environmental destruction. The prescriptive value of those legal frameworks could be critically diminished, and the resilience of the law as a normative framework may be threatened.